2021
DOI: 10.1016/j.ijchp.2021.100226
|View full text |Cite
|
Sign up to set email alerts
|

Modification of hostile interpretation bias and self-reported aggression in juvenile delinquents: A randomized controlled trial

Abstract: Background/Objective The social information processing model holds that aggressive behavior is closely related to the hostile interpretation of ambiguous social cues, suggesting the possibility that an intervention that reduces hostile interpretations could reduce aggression. This study in Mainland China evaluated the remediating effects of cognitive bias modification for interpretation (CBM-I) on the hostile interpretation bias and self-reported aggressive behaviors of male juvenile delinquents, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…As hypothesized, interpretation bias was positively correlated to CP and PPs. Those findings are in line with previous studies that indicated a hostile interpretation bias in children with conduct disorder [32-34]. Unexpectedly, the pro-social response access scale of GOSSIP did not show a significant correlation with the pro-social subscale of the SDQ.…”
Section: Discussion/conclusionsupporting
confidence: 92%
“…As hypothesized, interpretation bias was positively correlated to CP and PPs. Those findings are in line with previous studies that indicated a hostile interpretation bias in children with conduct disorder [32-34]. Unexpectedly, the pro-social response access scale of GOSSIP did not show a significant correlation with the pro-social subscale of the SDQ.…”
Section: Discussion/conclusionsupporting
confidence: 92%
“…In addition, a study showed that the effect of training on physical aggression was only significant in juvenile delinquents with a higher hostile interpretation bias at baseline. 51 Therefore, psychological characteristics at baseline may also be a critical factor. Future studies are required to explore the mechanism of emotional recognition training on aggression to find an effective behavioural intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In the face of the fact of illegal and criminal behavior, a harmful behavior is likely to be interpreted as the conduct of the perpetrator, that is, to make a negative moral judgment on the perpetrator (Doolan and Bryant, 2021). For most people, when they hear the facts of a crime, they have less chance and possibility to understand the whole process of the incident in detail, so it is easy to fall into the moral judgment of the perpetrator, believing that their moral level is low (Ren et al, 2021). The result is an inappropriate construction of the moral status of both parties under biased perceptions.…”
Section: Occupying Resource: Resource-based Self-oriented Motivationmentioning
confidence: 99%